Bicondylar Angle and its Relation with Length and Neck Length of Human Femur - Kharbuja, Rabita; Adhikari, Rashmi Manjushree; Shrestha, Anupama (Journal of Lumbini Medical College, 2018)
Introduction: Femoral bicondylar angle has immense importance from anatomical and clinical (forensic and anthropometric) point of view and is the characteristic feature of bipedal gait in humans. It is the angle between axis of femoral shaft and a line perpendicular to its transcondylar axis. The study was carried out to assess bicondylar angle and its relationship with femur length and neck length. Methods: Bicondylar angle, length, and neck length of available dry human femurs of unknown sex and age were measured using osteometric board and vernier caliper. Bicondylar angle between two sides were compared. Similarly, relation between the angle and femoral length and length of femoral neck was studied. Result: Bicondylar angle on right side was 8.65° (SD = 2.03) and on left side was 9.35° (SD = 2.05) and the different was not statistically significant (p = 0.08). On both sides, no significant correlation was found between bicondylar angle with femoral length and length of femoral neck. Conclusion: Mean bicondylar angle of right femur was 8.65° and that of left was 9.35° and the difference was not statistically significant. There was no significant relation between the angle and other two parameters. DOI: https://doi.org/10.22502/jlmc.v6i1.176